PEMANFAATAN TEKNOLOGI DIGITAL UNTUK PEMBERDAYAAN UMKM DESA KAPUTIHAN - Yani Sri Mulyani; Yanti Apriyani; Miftah Farid Adiwisastra; Atyla Azfa Al Harits; Fauziah Nur Madinah (Bajang Institute, 2025)
The use of digital technology for the empowerment of MSMEs can encourage the improvement of competitiveness and market access for business actors. In Kaputihan Village, Jatiwaras District, Tasikmalaya Regency, which has natural products and snack food production, technology has not yet been utilised as a medium to market the produced products. This community service activity is expected to help the community optimise online product marketing, increasing sales and reaching a wider market. The method used in this activity is a workshop training on the Pasar Kaputihan application for the community of MSME actors and village officials as application administrators. With the digital marketing training